As implicações da dinâmica do financiamento da educação nas desigualdades intermunicipais quanto ao gasto aluno no estado do Espírito Santo - Dubberstein, Flavia Costa Lima (2015)
This research aimed to analyze the implications of education funding dynamics in inter inequalities in student spending in the state of Espírito Santo. We question is about how much a student spend with education in the state of Espírito Santo. We question is about the institutional capacity of each municipality to provide the required step of education in the state of the Espírito Santo? The guarantee of educational provision from the legislation was established as the theoretical basis of the study, considering the Constitutional Amendment 59 of 2009, and using Pinto (2007; 2010; 2012; 2013; 2014) as the main interlocutor considering that it points to the viability of the right to public education from more spending on education. Our work is qualitative methodology and how we use the literature review from documentary research on the site of the Court of Espírito Santo (TCE-ES) and through the National Institute for Research in Education Anísio Teixeira (Inep).From the analysis of spending student practiced in the cities of these micro-regions, we understand that the 78 Espírito Santo municipalities during the analysis period, have financial capacity to ensure the educational provision for mandatory age group. We realize that there is a discrepancy regarding the educational provision in municipalities in the state of Espírito Santo, considering the amounts of spending student practiced in the years 2009-2013.